Sustainable OER-Enabled Pedagogy: A Conceptual Framework for Open Educational Resources, Renewable Assignments, and Equity-By-Design - Tran Minh Khoa Tran Minh Khoa (Kalam Practica Media, 2025)
This paper proposes a framework for sustainable OER-enabled pedagogy that integrates open educational resources (OER), renewable assignments, accessibility, and equity-by-design across four interdependent domains. OER adoption has grown substantially in recent years, driven by documented cost savings ranging from 90 to 200 per student per course and by meta-analytic evidence of modest but statistically significant improvements in student performance (d = 0.17–0.20). Yet adoption frequently underdelivers its educational promise when materials are curated without instructional coherence, when accessibility requirements are neglected, or when institutions lack the policy infrastructure and workload incentives necessary to sustain open practices at scale. OER-enabled pedagogy extends beyond cost reduction by leveraging open licenses to support renewable assignments, in which learners create shareable artifacts that contribute to public knowledge and community learning. Renewable work enhances motivation and positions students as knowledge producers, yet simultaneously introduces ethical responsibilities related to consent, privacy, inclusivity, and quality assurance that must be addressed proactively. Synthesizing research from instructional design, open education, accessibility standards, and implementation science, the paper proposes a framework with four domains: (a) instructional coherence and design quality, (b) renewable assignment design and learner agency, (c) accessibility and culturally responsive adaptation, and (d) institutional sustainability, encompassing policy incentives, infrastructure, and communities of practice. Three empirical tables present quantitative benchmarks drawn from published studies on OER learning outcomes, renewable assignment engagement, and institutional adoption rates. The paper argues that sustainable open education requires coordinated attention to pedagogy, ethics, and systemic institutional change, and offers practical implications for educators, instructional designers, librarians, and academic leaders.